1996
DOI: 10.1051/jp4:1996342
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of Bi2Sr2Ca2Cu3O10+δ Bicrystal Grain Boundary Josephson Junctions and SQUIDs

Abstract: Josephson junctions and SQUIDs on 36.8" SrTi03 bicrystal substrates were prepared from epitaxial Bi2Sr2Ca2Cu3010+8 thin films with critical temperatures around 95K. The current-voltage characteristics are well described by the resistively and capacitively shunted junction model. I,R, products of 50pV at 77K and 0.7mV at 4.2K have been reached. The I,(B) dependence is symmetric to B = 0 with an I, suppression of 90% in the first minimum. Nevertheless it turns out, that the junctions are inhomogeneous on a pm sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For the B2 samples, the grain boundary resistivity in all our samples are large. For B2HA750, GB = 1.01 Ωm, which is nearly 10 5 times large than equivalent numbers for B1HA750 and much higher than the bicrystal values of (3.6 − 4.0)× 10 −3 Ωm , reported by Frey et al [60] and Ohbayashi et al [61]. B2M30HA750 has 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A c c e p t e d M a n u s c r i p t 13 GB = 1.65×10 −2 Ωm, which is 10 2 times lower than microcrystalline B2HA750.…”
Section: The Resistivity Of the Grain Boundariesmentioning
confidence: 90%
“…For the B2 samples, the grain boundary resistivity in all our samples are large. For B2HA750, GB = 1.01 Ωm, which is nearly 10 5 times large than equivalent numbers for B1HA750 and much higher than the bicrystal values of (3.6 − 4.0)× 10 −3 Ωm , reported by Frey et al [60] and Ohbayashi et al [61]. B2M30HA750 has 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 A c c e p t e d M a n u s c r i p t 13 GB = 1.65×10 −2 Ωm, which is 10 2 times lower than microcrystalline B2HA750.…”
Section: The Resistivity Of the Grain Boundariesmentioning
confidence: 90%
“…Ivanov and co-workers revealed that in addition to the misorientation angle , the orientation of the main crystal axes with respect to the grain boundary has a decisive influence on the critical current density (Ivanov et al, 1998). Experiments with ϭ32°[001]-tilt boundaries performed at 4.2 K displayed a reduction of J c by a 5 These superconductors include doped La 2 CuO 4 (Kawasaki et al, 1993;Beck et al, 1996), Ag-doped YBa 2 Cu 3 O 7Ϫ␦ (Holzapfel et al, 2000), NdBa 2 Cu 3 O 7Ϫ␦ (Romans et al, 2001), Bi 2 Sr 2 CaCu 2 O 8ϩ␦ (Tomita et al, 1990;Mayer et al, 1993;Amrein et al, 1995;, Bi 2 Sr 2 Ca 2 Cu 3 O 10ϩ␦ (Ohbayashi et al, 1995;Yan et al, 1995;Frey et al, 1996b;Takami et al, 1996;Yoshida et al, 1997;Attenberger et al, 2001), Tl 2 Ba 2 CaCu 2 O 8ϩx (Cardona et al, 1993;Sarnelli et al, 1994;Y. F. Chen et al, 1996;Weaver et al, 1996), Tl 1 Ba 2 Ca 2 Cu 3 O x (Nabatame et al, 1994), HgBa 2 CaCu 2 O 6ϩ␦ (Gupta et al, 1994;Tsukamoto et al, 1998;Yu et al, 1999;Inoue et al, 2000;Adachi et al, 2001), and Nd 2Ϫx Ce x CuO 4 (Kawasaki et al, 1993;Kussmaul, Tedrow, and Gupta, 1993;Kleefisch et al, 1998;Schoop et al, 1999;Woods et al, 1999).…”
Section: Dependence On Grain-boundary Anglementioning
confidence: 99%
“…Grain-boundary resistivities of various high-T c superconductors plotted as a function of the grain-boundary misorientation angle. The data were compiled from the following sources: (Hg,Re)Ba 2 CaCu 2 O y :Tsukamoto et al (1998); Tl 2 Ba 2 Ca 1 Cu 2 O 8ϩ␦ :Weaver et al (1996); La 2Ϫx Sr x CuO 4ϩ␦ :Beck et al (1996); YBa 2 Cu 3 O 7Ϫ␦ : Hilgenkamp and Mannhart (2 Ca 1 Cu 2 O 8ϩ␦ :Frey et al (1996b).…”
mentioning
confidence: 99%